Unequal inequalities: Do progressive taxes reduce income inequality? - Denvil Duncan; Klara Sabirianova Peter (Institute for the Study of Labor (IZA), 2012)
This paper analyzes the effect of changes in structural progressivity of national income tax systems on observed and actual income inequality. Using several unique measures of progressivity over the 1981-2005 period for a large panel of countries, we find that progressivity reduces inequality in observed income, but has a significantly smaller impact on actual inequality, approximated by consumption-based GINIs. We show empirically that the differential effect on observed vs. actual inequality is much larger in countries with weaker legal institutions. Substantial differences in inequality response to changes in top vs. bottom rates are also uncovered. The paper discusses implications of these results for flat tax policies.
Keywords: H2; I3; J3; O1; O2; 330; income inequality; Gini; personal income tax; structural progressivity; tax evasion; Steuerprogression; Einkommensverteilung; Einkommensteuer; Steuerkriminalität; Schätzung; Welt